Poważny brak rozeznania oceniającego co do istotnych praw i obowiązków małżeńskich (kan. 1095 n. 2 KPK) w świetle wyroku Roty Rzymskiej "coram" Erlebach z 16 października 2008 r. - Góralski, Wojciech (Ius Matrimoniale, 2013)
The author presents and comments on the Rotal decision (negative) issued in the second instance after appealing against the decision (positive) issued in the first instance (by one-man tribunal) by the respondent due to a serious lack of the evaluative analysis of both parties. The Rotal judge, after a thorough interpretation of the code-based expression discretio iudicii (including three elements), emphasizes that not always the lack of such analysis constitutes inability to come to a marital agreement. This inability shall constitute exclusively the serious lack of discretio iudicii, both in its internal and external aspects.